Embedding school cultures and climates that promote evidence-based practice implementation for youth with autism: A qualitative study. (May 2021) - Williams, Nathaniel J; Frederick, Lindsay; Ching, Alix; Mandell, David; Kang-Yi, Christina; Locke, Jill
Schools play a major role in delivering behavioral health services to autistic youth. School culture and climate are strong predictors of the extent to which these services incorporate evidence-based practices; however, little is known about how school leaders shape culture and climate. Drawing on the concept of culture and climate embedding mechanisms, we conducted a qualitative study to understand the ways in which school principals embed cultures and climates that support effective implementation of evidence-based practices for youth with autism. Semi-structured interviews with 32 teachers in schools that implemented three closely related evidence-based practices for youth with autism (discrete trial training, pivotal response training, and visual schedules) explored teachers' experiences regarding (a) implementation of the three evidence-based practices, (b) perceptions of school culture and climate, and (c) principals' behaviors, practices, and decisions that supported or detracted from the aspects of culture and climate that supported successful implementation. Thematic analysis detailed seven mechanisms that principals used to embed cultures and climates that shaped evidence-based practice implementation. These mechanisms represent actionable targets for school leaders and inform strategies to improve the implementation of evidence-based practices for youth with autism in schools. Lay abstract: Schools play a major role in providing services to youth with autism; however, not all schools use evidence-based practices, defined as interventions that are proven to improve youth well-being through rigorous research. School culture and climate are strong predictors of whether or not a school uses evidence-based practices; however, little is known about how principals can create school cultures and climates that support the use of these practices. This study interviewed 32 teachers in elementary schools that implemented three closely related evidence-based practices for youth with autism to better understand how principals create school cultures and climates that support effective services. Analysis of the teachers' responses identified seven strategies principals can use to create school cultures and climates that support the implementation of effective practices for youth with autism. The strategies include the following: (a) support teachers to obtain professional development focused on autism, (b) align performance expectations and evaluations with the needs of students with autism and evidence-based practice delivery, (c) allocate resources to ensure adequate staff, materials, and training are available to implement evidence-based practices, (d) be open and flexible to allow teachers to use the building and resources as needed to meet students' needs, (e) provide direct assistance, feedback, and coaching to troubleshoot challenges or involve outside experts to do so, (f) openly value the work of special education teachers and provide recognition to those who develop expertise in evidence-based practices, and (g) look for opportunities to integrate special and general education teachers and students to foster a truly inclusive climate.